2015
DOI: 10.1038/srep15401
|View full text |Cite|
|
Sign up to set email alerts
|

Direct and high throughput (HT) interactions on the ribosomal surface by iRIA

Abstract: Ribosomes function as platforms for binding of other molecules, but technologies for studying this process are lacking. Therefore we developed iRIA (in vitro Ribosomes Interaction Assay). In approach I, Artemia salina ribosomes spotted on solid phase are used for binding picomoles of analytes; in approach II, cellular extracts allow the measurement of ribosome activity in different conditions. We apply the method to analyze several features of eIF6 binding to 60S subunits. By approach I, we show that the off-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 24 publications
(34 reference statements)
1
25
0
Order By: Relevance
“…This model is consistent with the accumulation of free 60S that we observed (Fig 2A). We recently developed a Ribosomes Interaction Assay (Fig 2G), able to quantify eIF6 binding sites on the 60S [40]. We immobilized equal ribosomes from Sbds R126T/R126T and wild type cells, and measured eIF6 binding sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is consistent with the accumulation of free 60S that we observed (Fig 2A). We recently developed a Ribosomes Interaction Assay (Fig 2G), able to quantify eIF6 binding sites on the 60S [40]. We immobilized equal ribosomes from Sbds R126T/R126T and wild type cells, and measured eIF6 binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…iRIA assay was performed as described in [40]. Briefly, 96-well plates were coated with a cellular extract diluted in 50 μL of PBS, 0,01% Tween-20, O/N at 4°C in humid chamber.…”
Section: Methodsmentioning
confidence: 99%
“…To assess whether increased transcription of genes related to ribosome biogenesis and rRNA processing observed in gene expression analysis experiments was accompanied by an effect in the translational machinery, we investigated changes in levels of free 60S subunits upon eIF6 overexpression. To this end, we performed the in vitro Ribosome Interaction Assay (iRIA) 33 . We found that the expression of eIF6 in larval eye discs (GMR>eIF6) led to a 25% reduction in free 60S sites when compared to control (GMRGAL4/+) ( Fig 6a).…”
Section: Eif6 Expression Reshapes the Transcriptome Increasing A Ribmentioning
confidence: 99%
“…In this study, we developed a novel method for finding modulators of eIF6 binding to the 60S subunit [34] and performed an automated screening of small compounds. Here, we describe the screening and identification of three compounds that have a biological activity that can modulate the binding of eIF6 to the 60S.…”
Section: Introductionmentioning
confidence: 99%